2010
DOI: 10.4049/jimmunol.0903811
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Upregulates Microglial Matrix Metalloproteinase-1 and -3 Expression and Secretion via NF-κB– and Activator Protein-1–Dependent Monocyte Networks

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 53 publications
4
66
0
Order By: Relevance
“…Doxycycline also suppressed TNF-a secretion, a key cytokine in the immune response to TB (7). TNF-a drives stromal cell MMP secretion via intercellular networks (22,26,35) and may also drive cachexia in TB (36), so doxycycline may have multiple immunomodulatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline also suppressed TNF-a secretion, a key cytokine in the immune response to TB (7). TNF-a drives stromal cell MMP secretion via intercellular networks (22,26,35) and may also drive cachexia in TB (36), so doxycycline may have multiple immunomodulatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of MMP-9 was the most readily detected, though the secretion of the other MMPs may not have been detected due to the relative insensitivity of casein zymography to detect MMP-1, -3 and -7 [19]. More recently, investigating central nervous system TB, we have found that monocyte-microglial cell networks upregulate MMP-1 and -3 [39].…”
Section: Mmps Driven By Intercellular Networkmentioning
confidence: 94%
“…In lymph node TB, both epithelioid macrophages and multinucleate giant cells express MMP-9 [37,38]. In CNS TB, MMP-1, MMP-3 and MMP-9 expression has been demonstrated in cerebral TB granulomas [39,40]. In addition, astrocytes are a significant source of MMP-9 [41].…”
Section: Defining the Mmps Involved In The Pathogenesis Of Tbmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that numerous systemic diseases (such as Sjö gren syndrome) and their treatments (medications, head and neck radiation, chemotherapy) contribute significantly to salivary gland hypofunction. [3][4][5][6] Whole saliva is a mixed fluid that derives predominantly from 3 pairs of major salivary glands: the submandibular (SMG), the parotid, and the sublingual glands. Approximately 90% of total salivary volume results from the activity of these 3 pairs of glands, with the bulk of the remainder from minor salivary glands located at various oral mucosal sites.…”
Section: Introductionmentioning
confidence: 99%